2009
DOI: 10.1163/156854109x428016
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific duplex PCR for the detection of Pratylenchus penetrans

Abstract: ITS1, the 5.8S rRNA gene and ITS2 of the rDNA region were sequenced from 20 different Pratylenchus species. Additionally, the same region was sequenced from seven populations of P. penetrans. After purifying, cloning and sequencing the PCR products, all sequences were aligned in order to find unique sites suitable for the design of species-specific primers for P. penetrans. Since ITS regions showed variability between and even within populations of P. penetrans, only three small DNA sequences were suitable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…(Castillo and Vovlas 2007). Speciesspecific PCR assay is a popular method for detecting root-lesion nematodes (Setterquist et al 1996;Uehara et al 1998a, b;Al-Banna et al 2004;Waeyenberge et al 2009;De Luca et al 2012;Palomares-Rius et al 2014). The species-specific duplex PCR system designed for P. parazeae n. sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Castillo and Vovlas 2007). Speciesspecific PCR assay is a popular method for detecting root-lesion nematodes (Setterquist et al 1996;Uehara et al 1998a, b;Al-Banna et al 2004;Waeyenberge et al 2009;De Luca et al 2012;Palomares-Rius et al 2014). The species-specific duplex PCR system designed for P. parazeae n. sp.…”
Section: Discussionmentioning
confidence: 99%
“…Species specific primers: universal primers concentrations were 0.2: 0.2, 0.2: 0.08, 0.2: 0.04, 0.2: 0.02, 0.4: 0.08 or 0.4: 0.04 μM, respectively. One optional combination was obtained based on the criteria mentioned by Waeyenberge et al 2009. Finally, the optimized duplex PCR included 25 μl of sterile water, 1× PCR reaction buffer, 2 mM MgCl 2 , 200 μM of each dNTP, 0.2 μM of primers PpzF and PpzR, 0.04 μM of primers D3A and D3B, 1 U Ex Taq DNA Polymerase (TAKARA, Dalian, China) and 2 μl template DNA, was applied using PCR programme of initial denaturation at 94°C for 5 min, 35 cycles at 94°C for 30 s, 58°C for 30 s and 72°C for 40 s, followed by 72°C for 7 min.…”
Section: Duplex Pcr With Species Specific Primersmentioning
confidence: 99%
“…In particular, sequence analyses of the ITS containing region has allowed the assessment of heterogeneity among species, even for those that are closely related, as it evolved faster than the D2-D3 expansion segments of 28S rDNA and accumulated more substitution changes. The ITS loci are also particularly suited to the development of diagnostic PCR tools because they are repetitive and undergo sequence homogenisation, factors linked to the efficiency, sensitivity and specificity of amplification (Gasser et al 2008;Waeyenberge et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…However, several authors (Al-Banna et al 1997;Duncan et al 1999;De Luca et al 2004a;Subbotin et al 2008) argued that the D2-D3 expansion segments do not contain sufficient phylogenetic signal to resolve relationships among Pratylenchus nematodes at species level because of the existence of cryptic or complex species, which are morphologically indistinguishable but genetically divergent, as recently reported for members of this genus (De Luca et al 2010). More recent studies using ITS-rDNA demonstrated the usefulness of this approach for identification and phylogenetic reconstruction within the genus Pratylenchus (Waeyenberge et al 2009;Palomares-Rius et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…DNA was ex tracted as described by Holterman et al (2006). For many of the isolates DNA was available (all vermiform stages) as it had been used in another study (Waeyenberge et al, 2009). The Moroccan populations, viz., P penetrans, P. thornei and P. pseudocoffeae, were identified on the basis of their morphology, morphometries and D2D3 28S rRNA gene sequences.…”
Section: Nematode Populations and Dna Extractionmentioning
confidence: 99%